IMPLEMENTASI PROJECT BASED LEARNING DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 1 SEKADAU HULU - Julianto, Gregorius; Firmansyah, Andang; Rudiyanto, Yustinus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Senior High School 1 Sekadau Hulu has implemented Project-Based Learning (PjBL) in history learning through the creation of history learning videos by students. This implementation still tends to be conventional, and the planning is still not structured and implemented optimally. So, this study aims to describe the implementation of Project-Based Learning in history learning at Senior High School 1 Sekadau Hulu, which includes the planning, implementation, supporting and inhibiting factors, and project assessment evaluation stages. The study used a descriptive qualitative method through interviews, observation, and documentation. The results showed that in the planning stage, teachers developed teaching modules according to the Independent Curriculum by integrating PjBL through video-making projects that were in line with learning competencies. In the implementation stage, students were divided into groups of 5–6 people, with group leaders determined by the teacher and project topics determined by the teacher. The teacher acted as a facilitator, utilizing textbooks and the internet as learning resources. The project was implemented for two weeks. Supporting factors included the availability of textbooks, Wi-Fi, the school library, and student cooperation, while inhibiting factors included limited infrastructure, student time management, and teacher resources. The evaluation was carried out using a process and product assessment rubric, with the average student score being above 75 in the good category.